Technological requirements and challenges of body area networks - Jinzhao LIN; Tong BAI; Guoquan LI; Yu PANG (物联网学报)
With the development of ubiquitous networks and huge requirements of tele-medicine,an emerged new technology of body area network (BAN) has attracted extensive attention.BAN system could be used for medical,personal health and entertainment applications by implanting wireless sensors into or around the human body,which realized real-time detection and diagnosis of physical vital signs.However,BAN had more stringent requirements on power consumption,quality of service (QoS),security performance and other specifications.Based on its technological requirements,the research status and development trends of key technologies were discussed deeply,such as information perception of vital signs,wireless transmission,information security and integrated circuit design,and the faced challenges in applications were analyzed.